Pathways to the therapist paragon: a decolonial grounded theory - Bergkamp, Jude; O’Leary Sloan, Maeve; Krizizke, Jack; Lash, Malea; Trantel, Noah; Vaught, Jason; Fulmer, Tessa; Waite, Ilana; Martin, Abigail M.; Scheiderer, Cynthia; Olson, Lindsay (Frontiers in Psychology, 2023)
Introduction While many professional associations within clinical and counseling psychology have made an aspirational call for clinician awareness of social position, there is a lack of research into how socially-conferred privilege impacts psychotherapy. Specifically of interest is the differences in race and gender within the therapeutic dyad, in which there is a BIPOC (Black, Indigenous, and Persons of Color)/white1 or male/female-identified dynamic. Method The authors utilized a Grounded Theory approach to analyze qualitative interviews with practicing psychologists to construct a process model regarding how socially-conferred privileged identity domains impact the therapeutic relationship and the participants’ professionalization process. Results The analysis identified the core conceptual theme of the Therapist Paragon, representing an idealized version of what a perfect therapist should be. This replicated the foundational figures of our field - primarily older, white men. The process model consisted of two distinct pathways toward the Therapist Paragon, one for BIPOC psychologists and one for white psychologists. The female BIPOC pathway consisted of imposter syndrome, persistent feelings of inadequacy, and tendencies to over-credential their professional identity to seek credibility in the eyes of clients and colleagues. The white pathway consisted of down-playing whiteness and attempting to initially modify behavior toward client cultural norms. Discussion The results point to a distinct professionalization and practice process for BIPOC psychologists compared to white counterparts. This dynamic may have implications beyond increasing support for BIPOC clinicians specifically, but instead indicate a lack of acknowledgement of the psychological impact of socially-conferred privilege in the psychotherapy enterprise overall. Recommendations are offered for revisions to training models, continuing education, and supervision/consultation.